Expression and prognostic significance of fibronectin and matrix metalloproteases in breast cancer metastasis. Issue 4 (28th November 2013) - Fernandez‐Garcia, Belen; Eiró, Noemí; Marín, Laura; González‐Reyes, Salomé; González, Luis O; Lamelas, Maria Luz; Vizoso, Francisco J
<x xml:space="preserve">Abstract</x> Aims Fibronectin (FN) has attracted interest in cancer research, owing to its role in tumour progression. The aims of this study were to investigate the expression and clinical relevance of FN in breast cancer, and to explore its relationship with the expression of matrix metalloproteases (MMPs) and their inhibitors (TIMPs). Methods and results An immunohistochemical study was performed using tumours from 110 breast cancer patients, with tissue arrays and specific antibodies against FN, MMP‐7, MMP‐9, MMP‐11, TIMP‐1, and TIMP‐2. The results indicated that FN expression was related to tumour size, histological grade, and MMP‐9 expression. Tumours with high FN expression by tumour cells were significantly associated with a higher probability of metastasis, poorer overall survival, and expression of MMP‐7, MMP‐9, MMP‐11, TIMP‐1 and TIMP‐2 by mononuclear inflammatory cells (MICs). In addition, the combination of FN expression by tumour cells and MMP‐11 by MICs was strongly associated with distant metastasis development. Conclusions Breast carcinomas with distant metastasis frequently have tumour cells expressing intracellular FN. There is a strong association between FN expression by tumour cells and MMP or TIMP expression by stromal MICs, and this may represent crosstalk that is of prognostic relevance in breast cancer.